2017
DOI: 10.4049/jimmunol.1601223
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Cleavage of Cytokines and Chemokines by the Human Mast Cell Chymase and Neutrophil Cathepsin G

Abstract: Human mast cell chymase (HC) and human neutrophil cathepsin G (hCG) show relatively similar cleavage specificities: they both have chymotryptic activity but can also cleave efficiently after leucine. Their relatively broad specificity suggests that they may cleave almost any substrate if present in high enough concentrations or for a sufficiently long time. A number of potential substrates have been identified for these enzymes and, recently, these enzymes have also been implicated in regulating cytokine activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 38 publications
(50 reference statements)
0
70
0
Order By: Relevance
“…Alternatively, the lack of mMCP-4 may result in less numbers of intestinal Tuft cells, since epithelial cell migration is reduced in the mMCP-4 −/− mice [34]. We and others have shown that mMCP-4 can activate the pro-cytokine IL-33 and that human and mouse chymase then degrades active IL-33, which is likely to reduce excessive inflammation in the stressed tissue [70][71][72]. The observed increased IL-25 expression and determination of intestinal protein levels of IL-25 and IL-33 during infection with G. intestinalis warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the lack of mMCP-4 may result in less numbers of intestinal Tuft cells, since epithelial cell migration is reduced in the mMCP-4 −/− mice [34]. We and others have shown that mMCP-4 can activate the pro-cytokine IL-33 and that human and mouse chymase then degrades active IL-33, which is likely to reduce excessive inflammation in the stressed tissue [70][71][72]. The observed increased IL-25 expression and determination of intestinal protein levels of IL-25 and IL-33 during infection with G. intestinalis warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, activated MCs can modulate IL‐33 activity via the secretion of serine proteases. Human MC chymase and tryptase selectively cleave full‐length human IL‐33 (IL‐33 1‐270 ) and generate the active forms: IL‐33 95‐270 , IL‐33 107‐270 , and IL‐33 109‐270 , which were 30‐fold more potent than full‐length protein for activation of group‐2 innate lymphoid cells (ILC2s) ex vivo . It was also shown that cleavage of full‐length IL‐33 by tryptase contributes to the allergic airway inflammation in vivo .…”
Section: Alarmin Receptorsmentioning
confidence: 99%
“…It exacerbates allergic bronchoconstriction by increasing secretion of serotonin from MCs and IL‐33 has also been reported to induce Th17‐mediated airway inflammation via MCs. Vice versa, MCs release IL‐33 under IgE/antigen stimulation and the generation of potent forms by the cleavage of proteases, thus leading to a positive feedback of IL‐33 activity.…”
Section: Alarmin Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Connective tissue mast cells also express an MC-specific carboxypeptidasecarboxypeptidase A3 (Cpa3). These proteases have been shown to inactivate snake, bee, and scorpion toxins; regulate blood pressure by angiotensin II generation; and control inflammation by cleaving a selective panel of cytokines [1,12,[16][17][18][19][20]. Mast cell proteases likely have several other important physiological functions, including connective tissue turnover and regulating coagulation [21,22].…”
Section: Introductionmentioning
confidence: 99%